Squamous cell carcinoma arising within hidradenitis suppurativa: a literature review. (2nd June 2021) - Sachdeva, Muskaan; Mufti, Asfandyar; Zaaroura, Hiba; Abduelmula, Abrahim; Lansang, Rafael Paolo; Bagit, Ahmed; Alhusayen, Raed
Abstract: Squamous cell carcinoma (SCC) can present as a rare complication of longstanding hidradenitis suppurativa (HS) lesions. Limited data exist on characteristics and outcomes of SCC development within HS lesions. The purpose of this review is to conduct a literature review of previously reported cases of SCC development in pre‐existing HS lesions. EMBASE and MEDLINE searches were conducted in OVID on June 25, 2020, to yield 59 studies. Of the 95 patients (mean age: 52.9 years) who developed a total of 122 SCCs within HS lesions, the majority were males (77.9%, n  = 74/95). The most common sites of SCC were the gluteal region (47.5%, n  = 58/122), the perianal region (18.9%, n  = 23/122), and the genitals (13.9%, n  = 17/122). The mean duration between HS onset and SCC development was 25.5 years. Of the patients that had outcomes reported, 54.0% ( n  = 34/63) experienced SCC metastasis, 43.1% ( n  = 28/65) experienced SCC recurrences, and 58.7% ( n  = 44/75) experienced a mortality outcome. The most common documented reasons for death included metastasis (34.1%, n  = 15/44) and sepsis (13.6%, n  = 6/44). Patients with longstanding HS lesions can develop SCCs with a high rate of metastasis and mortality. Thus, chronic HS lesions, especially in the gluteal, perianal, genital, and perineal regions, should be monitored regularly for timely SCC diagnosis and management.